IMPLEMENTATION OF ANIMATED VIDEO – BASED ENGLISH LEARNING FOR SEVENTH GRADERS: A CASE STUDY AT MTS. MAARIF NU TUBAN - Fauzi, Ali; Umam, Hibrul; Wildan Annihrir, Achmad; Fauzi, M (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
Teaching English at Islamic Junior High School in the digital era needs habit and Information-Technology knowledge, therefore English teacher must be able to keep up with the times. He must also use suitable materials, method, strategy and modern- attractive media. However, digital media like animated video is rarely used in the suburban private Secondary School like Islamic Junior High School, MTs. Maarif NU Tuban because of the limited facility the school has. Because of it, the researcher is interested to discuss it by choosing the title of research, “Implementation of Animated Video-Based English Learning for Seventh Graders: A Case Study at MTs. Maarif NU Tuban.” The researcher wants to know and to describe how the teacher teaches, what approach, strategy, method and media he uses during the process of teaching and learning. The research is qualitative research in form of case study. The approach he uses is phenomenological approach in which the researcher observes the facts and phenomena during the teaching of English and he then describes them. The data is in form of information from the teacher, teaching guideline, animated video and the facts happening in the classroom during the learning of English and the source of data is taken from You tube, interview with the teacher and from the guide books. The method of research is descriptive-qualitative method meaning the researcher just describes his data and his finding during the process of teaching-learning. The result of the research shows that teacher has taught the students well and successfully. He uses the method of speech, Q and A /discussion and role play; he applies scientific approach, and model of discovery learning; he uses learning media of animated videos supported by Guide books or handbooks he has determined, instrument of learning LCD Projector or handphone, and manages the class and time of learning well. The students are enthusiastic to join the lesson, motivated to train, do the homeworks and can understand the lesson optimally.